Dynamics of Parenting Styles on the Development of Dark Personality Traits: A Narrative Review - Masykuroh, Maryam Abidah; Poerwandari, Elizabeth Kristi (Utan Kayu Publishing, 2025)
The main focus of this narrative review is to reveal an explanation of how certain parenting styles impact the development of certain dark personality traits in individuals, as well as identify various forms of undesirable behavior as outcomes of dark personality traits. Researchers agree that in addition to genetic factors, an individual’s dark personality is influenced by environmental factors. Based on a review of the literature, the dynamics of the influence of parenting styles on the development of dark personality traits in individuals can be explained through the perspectives of evolutionary psychology theory, life history theory, self-determination theory, and social learning theory. In addition, it can be concluded that some outcomes of dark personality are in the form of various types of undesirable behavior.